2000
DOI: 10.1128/aac.44.11.2979-2984.2000
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of the tet (M) Gene in Tetracycline-Resistant Clonal Lineages of Streptococcus pneumoniae

Abstract: The aim of the present study was to examine the stability and evolution of tet(M)-mediated resistance to tetracyclines among members of different clonal lineages of Streptococcus pneumoniae. Thirty-two tetracyclineresistant isolates representing three national (Spanish serotype 14, Spanish serotype 15, and Polish serotype 23F) and one international (Spanish serotype 23F) multidrug-resistant epidemic clones were all found to be tet(M) positive and tet(O), tet(K), and tet(L) negative. These isolates all carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(77 citation statements)
references
References 45 publications
(29 reference statements)
6
68
3
Order By: Relevance
“…Thirteen tet(M)-containing strains were fully susceptible to tetracycline, suggesting the presence of a nonfunctional tetracycline resistance gene. A similar observation has previously been reported by Doherty et al (10).…”
Section: Discussionsupporting
confidence: 79%
“…Thirteen tet(M)-containing strains were fully susceptible to tetracycline, suggesting the presence of a nonfunctional tetracycline resistance gene. A similar observation has previously been reported by Doherty et al (10).…”
Section: Discussionsupporting
confidence: 79%
“…So far, no other tetracycline resistance determinants have been on May 11, 2018 by guest http://jcm.asm.org/ described; therefore, the underlying mechanism remains unclear. Also in line with the Vietnamese study is the isolation of tet(M)-containing but tetracycline-susceptible strains in Greece, suggesting the presence of a nonfunctional or unexpressed tetracycline resistance gene (2,9). A similar phenomenon was seen for the PBP genes.…”
Section: Discussionsupporting
confidence: 59%
“…Comparative sequence analysis of tet(M) in several mycoplasma isolates from Russia showed that the gene was completely identical in 11 of 13 M. hominis clinical strains (Soroka et al, 2002). By contrast, using a high-resolution restriction analysis, tet(M) variation in S. pneumoniae was shown to occur at both the inter-and intraclone levels (Doherty et al, 2000), suggesting that tet(M) may evolve differently depending on the bacterial species. However, comparative analyses of several S. pneumoniae tet(M) sequences available in GenBank revealed a divergence rate of no more than 2 % (data not shown).…”
Section: Discussionmentioning
confidence: 97%